Präferenzen für eine nachhaltige Stromversorgung - Kai Rommel; Julian Sagebiel (ISM Research Journal, 2017)
– Increasing the share of renewable energies requires the extension of grid capacity and additional storage possibilities. Although load shifting has been identified as a key instrument to relief the overloaded grid, technologies that enable load shifting decentrally have hardly penetrated the electricity market. In this paper, we apply a discrete choice experiment to investigate preferences and willingness to pay values for micro-cogeneration, a technology that has huge potential to reduce costs and CO2 emissions for heating. Our study includes home-owners as well as tenants to capture the overall market potential. Drawing from a sample of 412 adult Germans, we identified several drivers of willingness to pay for micro-cogeneration such as cost and CO2 saving potential, contract specifics and a feed-in tariff. Our results show that most people would be willing to invest in micro-cogeneration technologies but non-monetary obstacles, such as limited institutional support, hinder investment on a larger scale. We further identified several sources of preference heterogeneity, giving rise to the devel-opment of a large variety of products and incentive structures.
Keywords: 650